2015
DOI: 10.1002/prca.201400197
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of novel candidate urinary protein biomarkers for prostate cancer in a multiethnic cohort of South African patients via label‐free mass spectrometry

Abstract: Urinary proteomics is a promising route to PCa biomarker discovery and may serve as source of ethnic-related biomarkers of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 52 publications
1
26
0
Order By: Relevance
“…More strictly selected control groups are highly recommended, which recruit patients known to have a disease with a similar perturbation in biological function to the disease of interest. A good example of this is a recent study that sought biomarkers for prostate cancer and included patients with benign prostatic hyperplasia, patients with other uropathies, as well as a healthy control cohort [30]. Recruiting a related disease control group will bring a higher likelihood of discovering true unique markers with higher specificity to the disease of interest.…”
Section: Patient Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…More strictly selected control groups are highly recommended, which recruit patients known to have a disease with a similar perturbation in biological function to the disease of interest. A good example of this is a recent study that sought biomarkers for prostate cancer and included patients with benign prostatic hyperplasia, patients with other uropathies, as well as a healthy control cohort [30]. Recruiting a related disease control group will bring a higher likelihood of discovering true unique markers with higher specificity to the disease of interest.…”
Section: Patient Selectionmentioning
confidence: 99%
“…The identification of candidate protein biomarkers can be achieved by relative quantification through label-free or labelbased approaches. Label-free quantification compares proteins or peptides between different LC-MS runs, usually through spectral counting and peak area or intensity measurements [71][72][73][74]. Since no labeling reagent is involved, the sample preparation is often simpler and relatively inexpensive.…”
Section: Label-free Quantificationmentioning
confidence: 99%
“…PCa proteomics has been carried out in African-American populations [87, 88] but there are a limited number of studies among indigenous men of African descent. One such study identified 82 novel potential urinary biomarkers of PCa in a heterogeneous cohort of 45 South African patients composed of Indigenous, Mixed-Ancestry and Caucasian African PCa patients via label-free MS [89]. Among these 82 identified biomarkers, nine biomarkers were identified that suggested racial differences among the ethnicities in the cohort.…”
Section: Proteomics Biomarker Discovery In Africamentioning
confidence: 99%
“…These identified serological autoantibody responses could potentially be used in the construction of mini-arrays as point of care diagnostic tools as well as for therapeutic vaccine development for PCa in Africa. Many of these potential biomarkers have been reported in literature as being associated with other diseases, PCa as well as cancers in other human body organs; however, many are still yet to be described in PCa [89]. A comprehensive list which highlights the emerging potential biomarkers of PCa from those studies in terms of their source, methods used for their discovery and how far down the biomarker discovery pipeline they have moved, is provided in Tables 1A, 1B, 1C, 1D.…”
Section: Proteomics Biomarker Discovery In Africamentioning
confidence: 99%
“…These samples were processed routinely for shotgun discovery proteomics and analyzed using ultra-HPLC and mass spectrometry. Postanalytic statistical evaluation revealed a total of 73 potential PCa biomarkers as well as nine biomarkers which demonstrated potential ethnic trends in South Africa [27]. Two pooled samples were prepared for PRM using peptides from 15 PCa samples and 15 normal control samples, respectively.…”
Section: • • Sample Sourcementioning
confidence: 99%